2020
DOI: 10.31196/huvfd.801569
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Os Coxae in Horses Using Geometric Morphometry Method

Abstract: In contrast to normal morphometric measurements, geometric morphometry is a method that can explain the differences and variations on the x-y coordinates of the specified points on a 2D plane. In this method, two-dimensional samples, such as pictures or x-rays, are used. The study aims to investigate the right os coxae of 23 adults (12 males, 11 females) horses geometrically. Photographs were taken from each sample at 120 centimeters distance and landmarks were made on these samples. 13 determining landmarks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This indicates that the pelvis exhibits differences between sexes in terms of shape. In a geometric morphometric study focusing on sex differences and conducted on the coxae of horses (Gündemir et al., 2020b), it has been observed that some anatomical points show statistically significant differences between sexes. However, in this study, the photographs of the coxae were taken from a lateral perspective, and there are not many matching points with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the pelvis exhibits differences between sexes in terms of shape. In a geometric morphometric study focusing on sex differences and conducted on the coxae of horses (Gündemir et al., 2020b), it has been observed that some anatomical points show statistically significant differences between sexes. However, in this study, the photographs of the coxae were taken from a lateral perspective, and there are not many matching points with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Study on the wing shapes of vinegar flies (Gidaszewski et al., 2009), comparison on the shells of turtles (Duro et al., 2021), turkey (Gündemir, Özkan, Dayan, & Aydoğdu, 2020) and quail (Szara et al., 2022) cranium comparisons, study on horse os coxae (Gündemir et al., 2020b) can be given as examples for sexual dimorphism studies using geometric morphometry technique.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining os coxae with geometric morphometry are available in the literature (Gündemir, Özkan, İnce, et al, 2020). In the study performed in horses, it was said that the ventral endpoint of the coxal tuber and mid-end of the coxal tuber were more lateral in males.…”
Section: F I G U R E 8 Regression Of Shape Onmentioning
confidence: 99%
“…In studies in which mostly skulls were used, differences in shape between sexes were revealed as well as differences between species (Demircioglu, Demiraslan, et al, 2021; Gündemir, Özkan, Dayan, et al, 2020; Gürbüz et al, 2020, 2022; Szara et al, 2022). In these studies, it was reported that shape analysis was performed by using x‐ray images as well as 2D photographs (Gündemir, Özkan, İnce, et al, 2020). However, there are limited studies on shape analysis about the pelvis, which is an important structure in terms of shape (Waltenberger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important for anatomical and morphometric studies on the sheep breeds to reveal the breed-specific characteristics. In the literature, there are morphologic and morphometric studies on the metacarpus of different sheep breeds (Demiraslan, Gürbüz, Aslan, & Akbulut, 2015;Gündemir, Pazvant, Jashari, & Dayan, 2020;Gürbüz, Demiraslan, Kırbaş, & Aslan, 2018;Pazvant et al, 2015).…”
mentioning
confidence: 99%